Nitrous oxide effluxes from plants as a potentially important source to the atmosphere - Lenhart, Katharina; Greiner, Steffen; Keppler, Frank (The new phytologist, 2019)
The global budget for nitrous oxide (N2O), an important greenhouse gas and probably dominant ozone-depleting substance emitted in the 21st century, is far from being fully understood. Cycling of N2O in terrestrial ecosystems has traditionally exclusively focused on gas exchange between the soil surface (nitrification-denitrification processes) and the atmosphere. Terrestrial vegetation has not been considered in the global budget so far, even though plants are known to release N2O. Here, we report the N2O emission rates of 32 plant species from 22 different families measured under controlled laboratory conditions. Furthermore, the first isotopocule values (δ15N, δ18O and δ15Nsp) of N2O emitted from plants were determined. A robust relationship established between N2O emission and CO2 respiration rates, which did not alter significantly over a broad range of changing environmental conditions, was used to quantify plant-derived emissions on an ecosystem scale. Stable isotope measurements (δ15N, δ18O and δ15Nsp) of N2O emitted by plants clearly show that the dual isotopocule fingerprint of plant-derived N2O differs from that of currently known microbial or chemical processes. Our work suggests that vegetation is a natural source of N2O in the environment with a large fraction released by a hitherto unrecognized process.